INTRATRACHEAL INJECTION OF NICKEL CHLORIDE AND COPPER-ZINC SUPEROXIDE-DISMUTASE ACTIVITY IN LUNG OF RATS - Novelli, ELB; Rodrigues, N. L.; Ribas, B. O.; Curi, P. R. (Natl Research Council Canada, 1992)
Superoxide radical (O2-) is a free radical that may be involved in various toxic processes. Cu-Zn superoxide dismutase catalyses the dismutation of the superoxide free radical and protects cells from oxidative damage, and it has been used clinically. The concentration of Ni2+ and Cu-Zn superoxide dismutase activity were measured in lungs of rats at time intervals of 5, 12, 19, 26, 33, and 40 days following an intratracheal injection of 127 nmol of NiCl2. Nickel chloride increased nickel content and resulted in a significant increase of Cu-Zn superoxide dismutase activity in lungs. This elevation of Cu-Zn superoxide dismutase activity was highest on the 12th day (approximately threefold) and is at levels comparable to controls rats on day 40 onwards. Since Cu-Zn superoxide dismutase activity was increased in lung throughout our experimental period without corresponding increases of Cu2+ and Zn2+, we speculate that the elevation of Cu-Zn superoxide dismutase activity might be due to an increased half-life of the enzyme, induced by nickel.
Keywords: NICKEL CHLORIDE; INTRATRACHEAL; CU-ZN SUPEROXIDE DISMUTASE; LUNG